COULD THE INTERNATIONAL HUMAN RIGHTS LAW LEAD TO CHANGES IN THE BRAZILIAN CONSTITUTION? - Valverde, Thiago Pellegrini; Gundim, Wagner Wilson Deiró (Revista de Direito Brasileira, 2020)
This article aims to discuss the possibility of constitutional changes coming from the International Human Rights Law, both by virtue of decisions issued in the International Courts when the State has expressed adhesion, as by the international norms freely covenanted in the scenario of the international society, ratifying and internalizing them. There is a legal duty to conform internal norms to international standards for the protection of human rights, and such a duty can be carried out through constitutional change or through direct amendment of legal texts, including the constitutional text. For this purpose, what is proposed here is the adoption of a universalist and supranormative vision of human rights, aided by the control of conventionality of norms and by the abandonment of the classical view of sovereignty